QUALITY AND EFFICACY OF GENERAL ANESTHESIA VERSUS SEGMENTAL THORACIC SPINAL ANESTHESIA IN MODIFIED RADICAL MASTECTOMY SURGERY: A SINGLE-CENTER OBSERVATIONAL STUDY - GUPTA, NAMITA; AGARWAL, SONIA; GOYAL, GAURAV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Surgical resection remains the most important treatment modality for breast cancers. Recent research suggests that the choice of anesthesia technique might also have a role in the recurrence of the disease. We compared quality and efficacy of the conventional general anesthesia technique with segmental thoracic spinal (STS) anesthesia technique used in modified radical mastectomy. Methods: 60 American Society of Anesthesiologists II/III patients were divided into two groups Group C (Control group) and Group S (Study group). Group C patients were induced with standard anesthesia regimen while Group S patients were given STS at T4–T5 inter space with 1.5 mL of 0.5% hyperbaric levobupivacaine along with 15 µg of fentanyl with conscious sedation. Hemodynamics, pain score, time for first rescue analgesia, experience of anesthesiologist, surgeon, and patients were recorded. Results: Time for induction in group S is significantly longer (Group C 17.4±3.8 vs. 36.2±7.2 min, in Group S). The duration of surgery (56±13.6 min vs. 76.4±15.9 min) was also significantly longer, while reversal period was shorter in Group S (9.2±6.2 and 6.3±5.7 min). Modified Aldrete’s recovery score achieved quickly in Group C (16.8±4.9 vs. 29.7±9.8 min), but postoperative analgesia was better in Group S as first rescue analgesic sode required after 6.2±1.9 h in Gr. S while in Gr. C time duration was 4.9±1.3 h. Length of stay in hospital was more in Group S, (Group C 45.4±4.8 vs. Group S 56.3±8.5 [h]) while ease and comfort of surgeon anesthesiologist and patient satisfaction score were more in Group C. Conclusion: STS anesthesia is feasible for breast carcinoma surgeries but it is easier for surgeon and anesthesiologist to manage patient under general anesthesia. STS anesthesia has advantage in terms of early post-operative analgesia and will definitely be helpful in cases where patient is not fit for general anesthesia.